An instructive case of presumed brown snake (Pseudonaja spp.) envenoming. (September 2015) - Ou, Judy; Haiart, Sebastien; Galluccio, Steven; White, Julian; Weinstein, Scott A.
Abstract Context. Several species of medically important Australian elapid snakes are frequently involved in human envenoming. The brown snake group (Pseudonaja spp., 9 species) is most commonly responsible for envenoming including life-threatening or fatal cases. Several Pseudonaja spp. can inflict human envenoming that features minor local effects, but may cause serious systemic venom disease including defibrination coagulopathy, thrombocytopenia, micro-angiopathic hemolytic anemia (MAHA) and, rarely, paralysis. Pseudonaja envenoming is typically diagnosed by history, clinical assessment including occasional active clinical bleeding noted on physical examination (e.g. from venipuncture sites, recent cuts, etc.), and laboratory detection of coagulopathy (prolonged activated partial thromboplastin time [APTT]/INR, elevated D-dimer, afibrinogenemia and thrombocytopenia). Lack of verified identity of the envenoming snake species is a common problem in Australia and elsewhere. Identification and confirmation of the envenoming Australian snake taxon is often attempted with enzyme sandwich immunoassay venom detection kits (SVDKs). However, the SVDK has limited utility due to unreliable specificity and sensitivity when used to detect venoms of some Australian elapids. Antivenom (AV) remains the cornerstone of treatment, although there is debate concerning the recommended dose (1 vs. 2 or more vials) necessary to treat serious Pseudonaja envenoming. Envenomed patients receiving timely treatment uncommonly succumb, but a proportion of seriously envenomed patients may exhibit clinical or laboratory evidence of myocardial insult. Case details. An 88-year-old woman presented her dog to a veterinarian after it had sustained a bite by a witnessed snake, reportedly an eastern brown snake (Pseudonaja textilis, Elapidae). The woman became suddenly confused, and lost consciousness at the veterinary office. After transport to hospital, she denied any contact with the snake, but developed large haematomas at intravenous (i.v.) catheter insertion sites; blood tests revealed a severe defibrination coagulopathy, consistent with envenoming by a brown snake. An SVDK-tested urine sample was negative. A non-contrast CT of her head showed a minor subacute infarction of the left corona radiata. A twelve-lead ECG was normal, but her troponins were mildly elevated (39 ng/L). A diagnosis of brown snake envenoming was made and she received 2 vials of brown snake AV i.v., without adverse incident. Thirty min post AV her Glasgow Coma Score (GCS) had improved from 13 to 15 (normal). At 3.5 h post AV all bleeding from i.v. sites ceased, although her troponin T level peaked at 639 ng/L, supporting a diagnosis of non-ST elevated myocardial infarction (NSTEMI). Discussion. Severe brown snake envenoming may occur in the absence of a perceived bite, and AV is temporally associated with improvement in clinical findings and coagulopathy. However, severe envenoming by this species can be complicated by cardiovascular events that in the circumstance of incomplete or absent history may confuse the primary diagnosis and affect patient outcome.